Time-dependent behavior of NSM strengthened RC beams under sustained loading. (15th November 2021) - Moawad, M.; Baena, M.; Barris, C.; Torres, L.; Sallam, H.E.M.
Highlights: Twenty-eight RC and NSM FRP strengthened beams were cast and tested under 4 PB. Nineteen beams were investigated under different sustained loading conditions. Nine beams were tested under short term condition for comparison. Time-dependent and residual deflections are reported and discussed. The residual flexural strength was measured and discussed. Abstract: In this work, an experimental program comprising twenty-eight un-strengthened and NSM FRP strengthened RC beams was carried out to study their time-dependent behavior under sustained loading. At first, some beams were tested under short-term loading up to failure. Then, the others were subjected to long-term tests with different sequences. Each sequence included one or more of three stages: short-term test for two loading/unloading cycles up to service design load, sustained loading or aging for more than nine months, and short-term loading up to failure after removing the sustained loads. The studied parameters were CFRP area, tension steel reinforcement ratio, the ratio between the compression and tension steel ratio, concrete type, sustained load level, and loading history. Results in terms of the influence of the indicated parameters on the initial, time-dependent, and residual deflections, as well as residual flexural strength after removing the sustained load, are reported and discussed.